LEAP-GWU-2015 experiment specifications, results, and comparisons. Issue 113 (October 2018) - Kutter, Bruce L.; Carey, Trevor J.; Hashimoto, Takuma; Zeghal, Mourad; Abdoun, Tarek; Kokkali, Panagiota; Madabhushi, Gopal; Haigh, Stuart K.; Burali d'Arezzo, Francesca; Madabhushi, Srikanth; Hung, Wen-Yi; Lee, Chung-Jung; et al.
Abstract: LEAP (Liquefaction Experiments and Analysis Projects) is an effort to formalize the process and provide data needed for validation of numerical models designed to predict liquefaction phenomena. For LEAP-GWU-2015, one project within LEAP, an experiment was repeated at 6 centrifuge facilities (Cambridge University, Kyoto University, University of California Davis, National Central University, Rensselaer Polytechnic Institute, and Zhejiang University) and the results were shared and archived for the purposes of validation of numerical models. This paper describes the specifications for the LEAP-GWU-2015 experiment and compares the experimental results from the six facilities. The specified experiment was for uniform medium dense sand with a 5 degree slope in a rigid container subject to a ramped, 1 Hz sine wave base motion. The experiment was meant to be relatively simple to enable different facilities to produce comparable experiments. Although it cannot be claimed that identical experiments were precisely replicated on different centrifuges, it is argued that the results are similar enough that each experiment lends veracity to the set of results. A benefit of variability between experiments is that the variety enables a more general validation. Important lessons with regard to specification of future experiments for validation of numerical models are summarized. LEAP-GWU-2015 has demonstrated an approach that is a useful reference for future validation studies. Highlights: For LEAP-GWU-2015, an experiment was repeated at 6 centrifuge facilities. This paper compares the experimental results from the six facilities. The similarity of experiments enhances the value of the results. Lessons for future validation of numerical models are described.